A Dialogue with the Absurd: Remarks on Mikhail Volokhov’s Dramatic Works - Mięsowska, Lidia (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article presents an attempt to describe the oeuvre of the Russian and French playwright and theatre theoretician Mikhail Volokhov in the context of his relation to the Russian theatre of the absurd of the 1920s as well as to the 1950s western model of theatre of the absurd, represented by Samuel Beckett and Eugène Ionesco. The author also discusses Volokhov’s dramatic works in reference to the philosophy of existentialism.